Association of race and ethnicity to incident epilepsy, or epileptogenesis, after subdural hematoma. (24th November 2020) - Brown, Stacy C.; King, Zachary A.; Kuohn, Lindsey; Kamel, Hooman; Gilmore, Emily J.; Frontera, Jennifer A.; Murthy, Santosh; Kim, Jennifer A.; Omay, Sacit Bulent; Falcone, Guido J.; Sheth, Kevin N.
Abstract : Objective: To determine whether race is associated with the development of epilepsy after subdural hematoma (SDH), we identified adult survivors of SDH in a statewide administrative dataset and followed them up for at least 1 year for revisits associated with epilepsy. Methods: We performed a retrospective cohort study using claims data on all discharges from emergency departments (EDs) and hospitals in California. We identified adults (age ≥18 years) admitted from 2005 to 2011 with first-time traumatic and nontraumatic SDH. We used validated diagnosis codes to identify a primary outcome of ED or inpatient revisit for epilepsy. We used multivariable Cox regression for survival analysis to identify demographic and medical risk factors for epilepsy. Results: We identified 29, 342 survivors of SDH (mean age 71.2 [SD 16.4] years, female sex 11, 954 [41.1%]). Three thousand two hundred thirty (11.0%) patients had revisits to EDs or hospitals with a diagnosis of epilepsy during the study period. Black patients (n = 1, 684 [5.7%]) had significantly increased risk compared to White patients (n = 16, 945 [57.7%]; hazard ratio [HR] 1.45, 95% confidence interval [CI] 1.28–1.64, p < 0.001). Status epilepticus during the index SDH admission, although infrequent (n = 94 [0.3%]), was associated with a nearly 4-fold risk of epilepsy (HR 3.75, 95% CI 2.80–5.03, p < 0.001). Alcohol use, drug use, smoking, renal disease, and markers of injury severity (i.e., intubation, surgical intervention, length of stay, disposition other than home) were also associated with epilepsy (all p < 0.05). Conclusions: We found an association between Black race and ED and hospital revisits for epilepsy after SDH, establishing the presence of a racial subgroup that is particularly vulnerable to post-SDH epileptogenesis.